2007
DOI: 10.1177/1090198106294648
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Diet of Children: Development of Culturally Sensitive Measures

Abstract: Obesity is a growing global concern. Examining dietary habits of individuals can facilitate the development of important prevention approaches, which are needed to decrease the incidence of obesity and other related diseases and improve quality of life indices. Because food preferences and dietary habits vary across cultures, it is essential that prevention programs are based on specific populations. Using both ethnographic and quantitative methods, food-consumption patterns were investigated among 1,125 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Context relevant demographic, familial, and sociocultural variables discussed previously were identified for use in this study (8,22,23). These included maternal and paternal ethnicity of the child, caregiver and child's age and gender, caregiver's educational level, school lunch eligibility as indicated by the caregiver, household structure, history of prior participation in health education, and caregiver's perception of child's weight normalcy status.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Context relevant demographic, familial, and sociocultural variables discussed previously were identified for use in this study (8,22,23). These included maternal and paternal ethnicity of the child, caregiver and child's age and gender, caregiver's educational level, school lunch eligibility as indicated by the caregiver, household structure, history of prior participation in health education, and caregiver's perception of child's weight normalcy status.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…When responsiveness to basic tastants were assessed, participants identifying as Hispanics were more responsive to taste stimuli compared to non-Hispanics (15). Ethnicity can serve as an indicator of future dietary preferences as commonly consumed foods during childhood may influence food choices (5860). In our study, participants who identified as Hispanics had higher liking ratings for selected fruits, vegetables, and nuts, as well as higher HEI total fruits and sodium scores than those who identified as non-Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews in the field of healthy lifestyles and the prevention of overweight have emphasized the importance of culturally adapted interventions since parents' cultural background plays a role in their children's upbringing and feeding patterns,6,7 as well as obesity interventions for preschool children 8,9. Therefore, a “one-size-fits-all” approach to interventions is not sufficient 10–12.…”
Section: Culturally Sensitive Lifestyle Interventionsmentioning
confidence: 99%
“…Parental sensitivity, structure, and control in everyday eating situations leave their mark on young children's feeding patterns and are a strong predictor of eating behavior later in life 27. General parenting styles and specific feeding styles and food-related parenting practices are associated with the cultural background of families 7. The theoretical model proposed by Sleddens and colleagues,28 which focuses on upbringing to achieve lifestyle-related behavioral change in families, puts, therefore, parenting at the heart of interventions.…”
Section: Parenting In Lifestyle Interventionsmentioning
confidence: 99%
See 1 more Smart Citation